Gambaran Perilaku Ibu dalam Pemenuhan Gizi Seimbang pada Balita di Posyandu Mayang Kelurahan Sukorejo Kecamatan Sukorejo Kota Blitar - Isna Khusnul Khotimah (Journal of Ners and Midwifery, 2016)
Infants need a balanced nutritional intake in order to achieve optimal growth and development. The behavior of the parents, especially mothers may affect the fulfillment of balanced nutrition in infants. The purpose of this study was to determine the behavior of mothers in the fulfillment of balanced nutrition of infants in Posyandu Mayang Sukorejo villages District Sukorejo Blitar City. The research design was descriptive. The population was 38 mothers of children under five which were registered in the registration book of Posyandu Mayang. The sample was 38 mothers used saturation sampling technique. The data was collected by questionnaires. The Research was conducted on May 6-10, 2015. The results showed 65.8% had good knowledge, 57.9% had a positive attitude, 60.5% do the appropriate action in fulfillment of balanced nutrition of infants. The good knowledge of mother, a positive attitude and appropriate action may affect the fulfillment of balanced nutrition of infants. It was expected for mothers to increase their infant health by providing balanced nutrition.